The Place of Global Reality in Interdisciplinary Settings Using Modern Technology to Link Classrooms for Globalization - Morton, Chris; Mojkowski, Charles ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
The Global Education Model (GEM) Project, an undertaking of the Putnam-Northern Westchester Board of Cooperative Educational Services, is part of a larger effort to link students throughout the United States with their counterparts in other countries. GEM's educational technology is augmented by implementing, testing and analyzing nationally recognized programs to investigate the educational application of international telecommunications in classrooms, its effect on instruction, and the strategies required for successful, expanded school-based use. The model is based on the assumption that a global approach to education, with attention paid to cultural differences and an emphasis on interdisciplinary studies, will better prepare children to live, learn, and work as twenty-first century citizens. Formative evaluation of the GEM Project reinforces the importance of structured planning, educational applications, and coordination. The National Geographic Society's KidsNet and the University of Maryland's ICONS constitute the formal part of the GEM research process; informal programs have also been developed in the New York/Moscow Schools' Telecommunications Project using experience gained from the formal programs. Developing a telecommunications support system for a global education program requires attention to a comprehensive global education curriculum, powerful communications processes, and appropriate technology connections; staff development is a key ingredient of all three components. Global education provides a motivating experience for students and teachers to connect with the larger world of learning and work that is outside the school, and often outside their own community and country. (7 references) (DB)
ERIC Note: Paper presented at the Annual Conference of the Association for Supervision and Curriculum Development (San Francisco, CA, March 16-19, 1991).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Networks; Cultural Differences; Curriculum Enrichment; Educational Environment; Educational Technology; Elementary Secondary Education; Formative Evaluation; Global Approach; Interdisciplinary Approach; Telecommunications; Global Education; Reports, Descriptive; Speeches/Meeting Papers